Quaternary evolution of the Gulf of Izmit (NW Turkey):: a sedimentary basin under control of the North Anatolian Fault Zone - Dolu, Erdal; Gokasan, Erkan; Meric, Engin; Ergin, Mustafa; Gorum, Tolga; Tur, Hueseyin; Ecevitoglu, Berkan; Avsar, Niyazi; Gormus, Muhittin; Batuk, Fatmaguel; Tok, Bugser; Cetin, Oktay (SPRINGER, 2007)
The Quaternary evolution of the Gulf of Izmit, situated on the tectonically active North Anatolian Fault Zone (NAFZ), was investigated using seismic reflection, paleontologic, and sediment textural data. On the basis of seismic stratigraphic and sedimentologic-paleontologic interpretations, four depositional units were distinguished within the Plio-Quaternary sequence of the Gulf of Izmit. According to these data, Plio-Quaternary deposits supplied from the northern terrestrial area started to accumulate during a progradational phase, in a south-facing half-graben. A coarse-grained sedimentary unit prograding into the gulf from the south since 200 ka B.P. indicates a dramatic variation in the evolution of the gulf, with the initiation of a new strike-slip fault of the NAFZ and a corresponding uplift of the Armutlu Peninsula in the south of the gulf. During the evolution of this fault from a wide shear zone consisting of right-stepped strike-slip faults and pull-apart basins to a localized principal fault zone, sediments were deposited under the influence of northerly prograding terrestrial and shallow-marine conditions due to relative sea-level fluctuations in the Marmara Sea. During this period, the Gulf of Izmit was invaded mainly by Mediterranean and partly by Black Sea waters. In the latest glacial period, shallow areas in the gulf became subaerially exposed, whereas the central and western sub-basins of the gulf turned into lakes. The present evolution of the Gulf of Izmit is controlled by the after effects of the new rupture of the NAFZ and the estuarine nature of the gulf environment.
Keywords: MOMENT TENSOR INVERSION; EASTERN MARMARA REGION; SEA-LEVEL CHANGES; TECTONIC EVOLUTION; AUGUST 17; DEPOSITIONAL-ENVIRONMENTS; CHARACTERISTIC FEATURES; NEOTECTONIC STRUCTURES; WESTERN TURKEY; ACTIVE FAULTS; Geology; Oceanography